Comparative characterization of ARC-PVD ZrN and PEO hydroxyapatite coatings on pure Ti-6Al-4V substrates for biomedical applications - Garkusha, I.E.; McCulloch, C.A.; Nowakowska-Langier, K.; Wilczopolska, M.; Taran, A.V.; Kuprin, A.S.; Romaniuk, S.P.; Kravchenko, Ya.O.; Podhurska, V.Ya.; Proskurnyak, R.V. (Problems of Atomic Science and Technology, 2023)
The nanocrystalline films of zirconium nitride have been synthesized using ion-plasma vacuum-arc deposition technique on pure Ti-6Al-4V, whereas the hydroxyapatite coatings were deposited by the method of plasmaelectrolytic oxidation in alkaline electrolytes (hydroxyapatite + 1 М potassium hydroxide). Structure evaluation by X-ray diffraction analysis (XRD), scanning electron microscopy (SEM) with microanalysis (EDS) – were performed to study phase and chemical composition, surface morphology, microstructure of coatings. The formed HA PEO coatings with spheroidal structure contain the phases of CaTiO₃ calcium titanate, CaHPO₄ anhydrous dicalcium phosphate, and Ca₁₀(PO₄)₆(OH)₂ hydroxyapatite. It was revealed that ZrN single-phase coatings of cubic modification with finecrystalline grains of 20 nm in size were formed. This experimental study found that coating Ti-6Al-4V with ZrN and HA positively influences preosteoblast cell adhesion, which results in the almost complete coverage of the surface, along with a less number of cells grown on uncoated titanium surface.